2007
DOI: 10.1177/030089160709300305
|View full text |Cite
|
Sign up to set email alerts
|

The Technique of Intensity-Modulated Radiotherapy in the Treatment of Cholangiocarcinoma

Abstract: The intensity-modulated radiotherapy technique in bile duct carcinomas deserves further research and clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Wang et al (13) reported that GTV-to-CTV expansions of 4 mm for HCC are required to conceal any microinvasion and that this value could be reduced to 2 mm for about 95% patients with tumor dimensions #5 cm or AFP levels <400 mg/L. In past studies, CTV for IHC was defined as the GTV plus a margin of liver tissue that was $1 cm (6,(9)(10)(11) or 0.8 cm in length (12). Of these studies, one defined the target volume of four IHC cases (10), whereas the others considered the CTV of IHC was the same as that of liver metastases from colorectal cancer (9), locally advanced pancreatic cancer (11), or hepatocellular carcinoma (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al (13) reported that GTV-to-CTV expansions of 4 mm for HCC are required to conceal any microinvasion and that this value could be reduced to 2 mm for about 95% patients with tumor dimensions #5 cm or AFP levels <400 mg/L. In past studies, CTV for IHC was defined as the GTV plus a margin of liver tissue that was $1 cm (6,(9)(10)(11) or 0.8 cm in length (12). Of these studies, one defined the target volume of four IHC cases (10), whereas the others considered the CTV of IHC was the same as that of liver metastases from colorectal cancer (9), locally advanced pancreatic cancer (11), or hepatocellular carcinoma (12).…”
Section: Discussionmentioning
confidence: 99%
“…In past studies, CTV for IHC was defined as the GTV plus a margin of liver tissue that was $1 cm (6,(9)(10)(11) or 0.8 cm in length (12). Of these studies, one defined the target volume of four IHC cases (10), whereas the others considered the CTV of IHC was the same as that of liver metastases from colorectal cancer (9), locally advanced pancreatic cancer (11), or hepatocellular carcinoma (12). This assumption is unreasonable, because these four types of carcinoma have different origins and histopathologic characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petera et al (18) emphasized the importance of intensity-modulated radiotherapy in a study of patients with inoperable GBC or cholangiocarcinoma who were treated with a dose of 50-60 Gy/25 fractions; this treatment achieved a median overall survival time of 10.4 months. The NCCN guidelines (7) recommend concurrent chemoradiation as well, but advise that the therapeutic agents applied should be limited to either fluorouracil or capecitabine.…”
Section: Discussionmentioning
confidence: 99%